Heart Failure with Recovered Left Ventricle Ejection Fraction. Case Report: Insuficiencia cardíaca con fracción de eyección del ventrículo izquierdo recuperada. Reporte de caso | 左心室射血分数恢复的心力衰竭：病例报告 - Diaz Cucho, Omar Augusto (2024)
Heart failure with recovered ejection fraction is defined as the improvement of left ventricular systolic function (LVEF) to values ≥ 40%, after having presented a reduced LVEF (< 40%) at a previous time and ≥10% absolute improvement in LVEF. It is a chronic and dynamic condition with a high risk of relapse and deterioration, so close monitoring and optimal medical therapy are essential for its management. A case is presented of a young male patient with dilated cardiomyopathy with severe left ventricular systolic dysfunction, who with neurohormonal therapy for heart failure, showed rapid clinical recovery and improvement of ejection fraction and left ventricular remodeling. Further studies are needed to better understand this condition and its long-term treatment.